Workshop on writing improvement of AsarFonts product with Dewan Bahasa & Pustaka - Muhammad Hafiz Aswad, Ahmad Kamal (Penerbit UMP, 2012)
Technology Transfer Office (TTO), a unit under Universiti Malaysia Pahang's Reseacrh and Innovation Department, organised a workshop on writing improvement of AsarFonts product that aimed at further enhancing the value and quality was held on September 25-26.